THE EFFECTS OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY ON LEARNING INDEPENDENCE IN SENIOR HIGH SCHOOL STUDENTS - Yahya, Amrina Rosyada, N (Universitas Negeri Medan, 2024)
The purpose of this study was to examine the effect of emotional intelligence on learning independence in class XI students of SMA Negeri 20 Surabaya, examine the effect of self-efficacy on learning independence in class XI students of SMA Negeri 20 Surabaya, and examine the effect of emotional intelligence and self-efficacy on learning independence in class XI students. SMA Negeri 20 Surabaya, and examine the effect of emotional intelligence and self-efficacy on learning independence in class XI SMA Negeri 20 Surabaya. on learning independence in class XI students of SMA Negeri 20 Surabaya. All students of class XI group C SMA Negeri 20 as many as 72 students were determined as the population in this study. The technique sampling technique used is a simple random sampling technique and a sample of 33 students is determined. determined a sample of 33 students. The approach in this study is a quantitative approach. Method collection method used is a questionnaire method with a data measurement scale in the form of a Likert scale. Likert scale. The hypothesis test used is an analytical test conducted with two stages of testing, namely the individual (partial) stage using the simple linear regression test and the joint (simultaneous) stage using the simple linear regression test. simple linear regression and the joint stage (simultaneous) using multiple linear regression tests. multiple linear regression tests. The result of this study is that there is no effect of emotional intelligence on learning independence in class XI high school students. State 20 Surabaya. There is a very significant influence of self-efficacy on learning independence in class XI students of SMA Negeri 20 Surabaya. There is a very significant effect of emotional intelligence and self-efficacy on learning independence in class XI SMA Negeri 20 Surabaya. learning independence in class XI students of SMA Negeri 20 Surabaya.